DEVELOPMENT OF A WEB-LIKE HEXAGON SHAPED ELECTROMAGNETIC ( EM ) TRANSMITTER - AHMAD, NUR AZLIZA (2011)
Direct detection of hydrocarbon using powerful electromagnetic (EM) source in seabed logging (SBL) application has remained a challenge because the size of recent transmitter is too huge. Thus, a new web like hexagon shaped transmitter is proposed as a new invention, this is due to its abilities in concentrating the EM field on its centre and minimizing the size of transmitter. Hexagon shape is the best design in terms of radiation power with 579.86% compared to the dipole transmitter by using Applied Wave Research (AWR) software. From Computer Simulation Technology (CST) software, web like hexagon shape with 20 turns shows the 215.85% increasing of electric field compared to 5 turns. Combination of EM transmitter with Ni0.8Zn0.2Fe2O4 toroid could enhance the EM field at the transmitter. Hence, web like hexagon shaped transmitter was constructed by using copper wire in diameter of 0.08 cm with 20 turns and comparison of magnetic field with and without magnetic feeder were conducted. Ni0.8Zn0.2Fe2O4 nanoparticles were successfully synthesized using self combustion technique. The samples were then sintered at 800 0C, 900 0C and 1200 0C for 4 hours respectively.